COD removal from semi-aerobic landfill leachate - Salwa, Mohd Zaini Makhtar; Naimah, Ibrahim; Mohammad Tamizi, Selimin (Universiti Teknologi Malaysia (UTM), 2011)
2nd International Conference and Workshops on Basic and Applied Sciences and Regional Annual Fundamental Science Seminar 2009 (ICORAFSS 2009) organized by Universiti Teknologi Malaysia, from 2nd - 4th June 2009 at Johor Bahru, Johor, Malaysia.